Gastropod fauna on organic falls at the Southwest Atlantic deep-sea - Souza, Bruno Henrique de Moraes e (2018)
The present study characterized the deep-sea gastropods community collected on whale bones and wood parcels artificially implanted in the deep Southwest Atlantic Ocean at 1500 and 3300 m depth for 23 months. A total of 5493 gastropods were collected and their distribution, abundance and diversity on substrates, depths and latitudes were calculated. Species richness and abundance of gastropods were higher in whale bones and deeper sites. Latitude did not seem to influence the distribution of mollusks. Five species were selected due to their abundance and possible ecological importance for further studies. Three were new species of the superfamily Abyssochrisoidea and were morphologically and genetically described (two Rubyspira and one Cordesia). The other two were Hyslogyrina rissoela (Heterobranchia) and Lusitanops cingulatus (Neogastropoda). To understand their feeding behavior and dispersal strategies were conduced stable isotopes analyzes, observations of gut content, and radular and larval shell morphology. Larval shell of most species suggested planktotrophic development. Animals on different growth stages were found. Gastropods presented a diversity of feeding strategies, such as bacterial mats grazing, predation and specialized bone eating. The overlap of this fauna with other chemosynthetic environments and with other basins corroborate with the ecological stepping stone hypothesis. Besides that, phylogenetic studies about Abyssochrysoidea were made. Their phylogenetic position within the Caenogastropoda are still uncertain but this group is considered closely related with Littorinidae. These snails are endemic from chemosynthetic environments, such as deep-sea hydrothermal vents, cold seeps and organic falls in the deep-sea. The genus Rubyspira is not settled at family level and no molecular studies were made for Cordesia. The present study also attempts to assign these groups phylogenetically. Concatenated COI, 16S, 18S and 28S and individual gene trees were constructed for maximum likelihood and Bayesian analysis. In all analyses the family Newtoniellidae were a sister group of Abyssochrysoidea. Morphological and genetic evidences suggest that Rubyspira and Cordesia are closer related to Abyssochrysos than to other provannid snails. The most accepted hypothesis is that Provannidae is paraphyletic. However, there are other ideas that indicates Rubyspira and Cordesia could be included in Abyssochrysidae or the Provannidae should be considered Abyssochrysidae. A morphologic revision of the superfamily should be made to better understand the relation within the group. Clades within the Abyssochrysoidea were always well supported and similar to those found in the literature. The position of Rubyspira and Cordesia within Abyssochrysoidea suggest whale bones and wood parcels did not play an evolutionary role as stepping stones for this group.